2014
DOI: 10.1590/s0100-67622014000500006
|View full text |Cite
|
Sign up to set email alerts
|

Influência da arquitetura foliar de miniestacas na propagação clonal de Eucalyptus

Abstract: Apesar do progresso da silvicultura clonal alcançado por meio da técnica de miniestaquia, pouco se avançou em relação às espécies recalcitrantes, sobretudo com relação ao manejo empregado em miniestacas. Com o objetivo de avaliar a influência da arquitetura de miniestacas na produção de mudas de quatro clones de Eucalyptus, foram realizadas avaliações nas três fases de produção de mudas: 1) Sobrevivência aos 30 dias em casa de vegetação, 2) Enraizamento aos 45 dias em casa de sombra; e 3) Aproveitamento final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
1
6
0
2
Order By: Relevance
“…A produção de clones por meio da miniestaquia permitiu a intensificação dos plantios clonais no país, em proporções comerciais. Essa metodologia fortaleceu um dos "mercados florestais", que foi o aparecimento de vários viveiros autônomos (não dependentes das firmas florestais), que começaram a oferecer ao mercado milhares de mudas clonais de Eucalyptus ao ano (BATISTA et al, 2014).…”
Section: Introductionunclassified
“…A produção de clones por meio da miniestaquia permitiu a intensificação dos plantios clonais no país, em proporções comerciais. Essa metodologia fortaleceu um dos "mercados florestais", que foi o aparecimento de vários viveiros autônomos (não dependentes das firmas florestais), que começaram a oferecer ao mercado milhares de mudas clonais de Eucalyptus ao ano (BATISTA et al, 2014).…”
Section: Introductionunclassified
“…The maintenance of leaves, especially the basal or subapical leaves, promote root formation. This positive effect is caused by the higher photosynthetic rate provided by the larger leaf area and a higher accumulation of carbohydrates (Batista et al, 2014;Souza et al, 2013). Given the superiority of the quality of the root system, it is recommended to maintain the entire leaf for P. peroba mini-cuttings.…”
Section: Types Of Mini-cutting and Leaves In The Rhizogenesis Of Paramentioning
confidence: 99%
“…A reduction of leaf area is adopted to reduce transpiration and avoid the 'umbrella effect', which can reduce irrigation efficiency (Alfenas et al, 2009;Xavier et al, 2013). Previous studies have shown that the maintenance of whole leaves provided maximisation of the rooting of mini-cuttings of Eucalyptus dunni clones, E. saligna and E. urophylla × E. globulus (Batista et al, 2014); Eucalyptus grandis × E. urophylla (Fernandes et al, 2018) and Eucalyptus benthamii (Mayer et al, 2018). Dias et al (2015) found that the presence of whole leaves led to significant gains in survival, rooting, and number of mini-cutting roots of Anadenanthera macrocarpa.…”
Section: Types Of Mini-cutting and Leaves In The Rhizogenesis Of Paramentioning
confidence: 99%
See 1 more Smart Citation
“…Among the methods of plant cloning is the minicuttings, a technique widely used to propagate clones of Eucalyptus species in Brazil, being characterized as one of the main factors, which contributed to the revolution of the country's clonal forestry on a commercial scale (Azevedo et al, 2015;Batista et al, 2014;Brondani et al, 2014;Fernandes et al, 2018;Rocha et al, 2015). Mini-cutting technique has been successfully used in the propagation of native forest species as an example, Cedrela fissilis (Xavier et al, 2003); Anadenanthera macrocarpa (Dias et al, 2015); Handroanthus heptaphyllus (Freitas et al, 2016); Tibouchina sellowiana (Fragoso et al, 2017); Peltophorum dubium (Mantovani et al, 2017); Cabralea canjerana (Burin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%